Convection in a warm conveyor belt : characterisation and impacts on altitude dynamics - Blanchard, Nicolas (CCSD, 2020)
Warm air conveyor belts (WCB) are ascending air streams in mid-latitude storms. They transport warm and moist air from the tropics to the high latitudes and are the site of most cloud diabatic processes. These processes modify the upper-level dynamics by injecting negative potential vortex (PV) anomalies into the WCB outflow, which reinforce the waveguide governing the general circulation. Their representation is a source of forecast errors downstream, especially over Europe. While WCBs are predominantly considered as slow continuous slantwise ascents, recent studies have revealed the existence of fast convective ascents in WCBs whose impact on upper-level dynamics is still debated. The reduction of forecast uncertainties motivated the NAWDEX field campaign over the North Atlantic in autumn 2016. During the campaign, the ascent region and the outflow of the WCB of the Stalactite cyclone were observed by an airborne Doppler radar and dropsondes. These observations are reproduced by a convection-permitting simulation carried out with the Meso-NH model, thanks to which a novel analysis combining Eulerian and Lagrangian approaches made it possible to characterize the complexity of the ascents in the WCB. The WCB ascent region is first studied. Three types of convective ascents are found and occur in a coherent and organized manner rather than as isolated cells. Two are caused by shallow convection related to the dynamics of the cold front and that of a low level jet. The third is due to mid-level convection, located on the western edge of the WCB between the low-level jet and the upper jet stream. It is the latter that feeds the anticyclonic branch of the WCB. The outflow of the WCB and its mid-level convection feed are then studied. An additional simulation is carried out for which the heat exchanges resulting from the cloud processes are cut off in order to highlight their impact on the upper-level dynamics. The reference simulation shows that the mid-level convection diabatically creates horizontal PV dipoles ...